BS IEC 61300-3-3. Fibre optic interconnecting devices and passive components. Basic test and measurement procedures. Part 3-3. Examinations and measurements. Active monitoring of changes in attenuation and return loss (15th June 2022) - British Standards Institution,
No abstract available